Scrapping subsidies during the financial crisis: Evidence from Europe - Nina Leheyda; Frank Verboven (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We study the effects of the car scrapping subsidies in Europe during the financial crisis. We make use of a rich data set of all car models sold in nine European countries, observed at a monthly level during 2005-2011.We employ a difference-in-differences approach, exploiting the fact that different countries adopted their programs at different points in time. We find that the scrapping schemes played a strong role in stabilizing total car sales in 2009: they prevented a total car sales reduction of 17.4% in countries with schemes targeted to low emission vehicles, and they prevented a 14.8% sales reduction in countries with non-targeted schemes. In contrast, the scrapping schemes only had small environmental benefits: without the schemes, average fuel consumption of new purchased cars would have been only 1.3% higher in countries with targeted schemes and 0.5% higher in countries with non-targeted schemes. We do not find evidence of crowding out due to substitution from non-eligible to eligible cars in countries with targeted schemes. Finally, we identify some competitive and trade effects from the schemes: domestic car producers benefited at the expense of foreign competitors in the countries where the schemes were not targeted.
urn:nbn:de:bsz:180-madoc-349036
Keywords: H25; L52; F14; 330; scrapping subsidies; economic assessment of state aid; financial crisis; automobile market